El 12 de octubre de 1964 en el País Vasco y su impacto transnacional en Venezuela - Marcela García Sebastiani (Mélanges de la Casa de Velázquez)
Studies on nationalism and territorial identities in the 20th century have focused attention on patriotic celebrations. The article examines the itinerant nature of the October 12 national holiday through the Spanish geography between the 20's and 60's. And it stops in the organization and performance of the Día de la Hispanidad in 1964 in the Basque country to analyze two dimensions. On the one hand, the political use that the Franco regime made of the symbol for its social diffusion in a climate of resistance to dictatorship and divisions of a clandestine Basque nationalism. On the other, the reactions that the celebration generated among anti-Franco exiles, the National Congress and public opinion in Venezuela. Analyzed in its political context and at transnational level, not only is the global dimension of the symbol confirmed, but also the efforts of the regime to strengthen it as an instrument of diplomatic and political socialization despite the questioning of its cultural policy, the disagreements among Basque exiles and the impact of the holiday day in Venezuelan politics.